(untitled) (Bangladesh Journal of Botany, 2025)
This study intended to assess advanced groundnut linesobtained from the cross between the Spanish bunch genotype,GPBD 4, which is resistant to rust and late leaf spot but highly susceptible to Aspergillusinfection and ICGV 2207, which istolerant to Aspergillusinfection. 198 advanced lines (F4-F6) along with their parents were evaluated for over three consecutive years (2019 to 2021) in Dharwad, Bagalkot and Belagavicomprisingfive distinct environments. Multivariate stability analysis was conducted to identify high yieldingand stablelines with resistance to Aspergillusflavusinfection. The results revealed highly significant variations(P<0.001) with high genotype × environment interaction (GEI) for pod yield and A.flavusresistance. AMMI and GGE biplot analyses identified 18 adaptable lines and five stable lines with high yields across the environments.Two lines (Lines 26 and122) showed stabilitywith high yields, while Line 65 showed minimal A.flavusinfection and is a valuable genetic resource in future resistance breeding programs. Bangladesh J. Bot. 54(3): 611-617, 2025 (September)